1985
DOI: 10.1002/bbpc.19850890214
|View full text |Cite
|
Sign up to set email alerts
|

A Neutron and X‐Ray Diffraction Study of the Binary Liquid Aromatic System Benzene‐Hexafluorobenzene I. The Pure Components

Abstract: A series of X‐ray and neutron diffraction experiments has been performed on liquid benzene and hexafluorobenzene in order to find out whether packing effects or electrostatic interactions are the structure determining factors. The results of the experiments are reported together with the determined molecular structures in the liquid phase. The agreement with the intramolecular parameters obtained by other methods is quite good. The existing descriptions of liquid benzene via computer simulations, structure mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
2

Year Published

1985
1985
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 38 publications
4
23
0
2
Order By: Relevance
“…A similar conclusion was drawn by Bartsch et al [6] using neutron scattering data measured at 25 C. Bochynski et al [7,8] qualitatively assigned the peaks at 410, 515 and 615 pm in the X-ray radial distribution function at 20 C to the stacked, perpendicular T and L arrangements, respectively. On the other hand, the result by a pulsed neutron total scattering experiment at room temperature supported the T configuration in which two molecules are inclined at about 73 [9].…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar conclusion was drawn by Bartsch et al [6] using neutron scattering data measured at 25 C. Bochynski et al [7,8] qualitatively assigned the peaks at 410, 515 and 615 pm in the X-ray radial distribution function at 20 C to the stacked, perpendicular T and L arrangements, respectively. On the other hand, the result by a pulsed neutron total scattering experiment at room temperature supported the T configuration in which two molecules are inclined at about 73 [9].…”
Section: Introductionsupporting
confidence: 75%
“…Much attention has been paid for its hexagonal molecular structure by many chemists and a lot of investigations have been done. The structural studies for liquid benzene have also been performed by the X-ray [1][2][3][4][5][6][7][8] and neutron scattering methods [6,[9][10][11], and computer simulation [10][11][12]. Narten [5] reported that the liquid structure of benzene at 25 C is similar to that found in the crystalline state.…”
Section: Introductionmentioning
confidence: 99%
“…The density (ρ) is the total mass over the current volume averaged over the simulations, (1) Experimental densities as a function of temperature were taken from refs 74,75 . The error bar of ρ equals the corresponding standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Weitergehende Aussagen uber Abstands-und Winkelabhangigkeit der zwischenmolekularen Korrelationen konnten nur durch wesentlich aufwendigere experimentelle Untersuchungen, etwa Rontgen-oder Neutronenbeugung [25,26] erhalten werden.…”
Section: Oounclassified